PENGEMBANGAN WISATA BENTENG PORTUGIS SEBAGAI DAYA TARIK WISATA DI KABUPATEN JEPARA - Kristianjaya, Octa; Suryaningsih, Margaretha; Mustam, Mohammad (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This research aims to identify and analyzes strategy conducted by localgovernment district Jepara in the tourism development of Benteng Portugis tocapable of being tourist attraction in the county of Jepara, as well as torecommend a new strategy in the tourism development of Benteng Portugis.The results of this research indicate that tourism development strategyundertaken by the department of tourism and culture has quite succeeded inJepara district, although there are some indicators which is considered lesssuccessful, but more will be considered successful by the writer. The indicatorwhich has not been successful is the existence of natural threats that exist becauseÂ of the layout of Benteng Portugis which is adjacent to the mountain and the sea.Conclusion in this research is based on tourism development strategyobject Jepara District by the Department of Tourism and Culture District ofJepara there is still an indicator that has not succeeded. The writer recommendsstrategy to correct the strategy has not worked.